Simultaneous detection of four flavonoids and two alkaloids in rat plasma by LC–MS/MS and its application to a comparative study of the pharmacokinetics between Abri Herba and Abri mollis Herba extract after oral administration. Issue 7 (5th February 2019) - Liu, Ruina; Yan, Wenying; Han, Qingjie; Lv, Tao; Wang, Xin; Liu, Xiaochen; Fan, Xueyan; Meng, Caifeng; Wang, Chunying
Abstract: Abri Herba and Abri mollis Herba both were important members of the Leguminosae family in southwestern China. Abri mollis Herba was often used as Abri Herba due to their proximity, but there are few studies on pharmacokinetics to compare their main identical active compositions. A sensitive and selective high‐performance liquid chromatography with tandem mass spectrometry method in the positive/negative electrospray ionization switching mode was developed and validated for the simultaneous analysis of four flavonoids and two alkaloids in rat plasma. The chromatographic separation was carried out on a C18 column with a gradient mobile phase consisting of methanol and 0.5% acetic acid. The detection of the target compounds was conducted in multiple‐reaction monitoring mode with a hybrid triple quadrupole linear ion trap mass spectrometer equipped with positive/negative ion‐switching electrospray ion source. The differences in pharmacokinetics were discovered, which indicated that the substitution between them is some degree of irrationality. The validated method was successfully applied to pharmacokinetic study of the six components in male rat plasma after oral administration of Abri Herba and Abri mollis Herba extract and the results in the study would provide a useful guide for the clinical application of Abri Herba with those in Abri mollis Herba.